Magnetoelectric properties of epitaxial Fe3O4 thin films on (011) PMN-PT piezosubstrates - Tkach, Alexander (2017)
We determine the magnetic and magnetotransport properties of 33 nm thick Fe3O4 films epitaxially deposited by rf-magnetron sputtering on unpoled (011) [PbMg1/3Nb2/3O3](0.68) - [PbTiO3](0.32) (PMN-PT) substrates. The magnetoresistance (MR), as well as the magnetization reversal, strongly depend on the in-plane crystallographic direction of the epitaxial (011) Fe3O4 film and strain. When the magnetic field is applied along [100], the magnetization loops are slanted and the sign of the longitudinal MR changes from positive to negative around the Verwey transition at 125 K on cooling. Along the [01 (1) over bar] direction, the loops are square shaped and the MR is negative above the switching field across the whole temperature range, just increasing in absolute value when cooling from 300 K to 150 K. The value of the MR is found to be strongly affected by poling the PMN-PT substrate, decreasing in the [100] direction and slightly increasing in the [01 (1) over bar] direction upon poling, which results in a strained film.